PENDAMPINGAN PERAN ORANG TUA UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI DI KB TUNAS HARAPAN KECAMATAN JOMBANG - Komarullah, Hafif; Afkarina, Faizatul; Latifah, Syifatul (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This project aims to increase the role of parents in supporting early childhood cognitive development through parenting activities and the use of bridging books at KB Tunas Harapan, Jombang District. The method used is Participatory Action Research (PAR) which involves parents and teachers actively in planning, implementation, evaluation, and reflection. The results showed an increase in parental involvement in children's learning process at home and the creation of effective communication between school and family. This activity has a positive impact on children's cognitive development and is expected to be replicated in other educational institutions.